The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/bf03325219
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and performance in older persons with musculoskeletal impairment: results of a pilot study with 9-month follow-up

Abstract: In this physically impaired sample, a 3- month exercise program, compared with unsupervised regular walking, was associated with improved performance, fitness and vitality after discharge, and to delayed physical decline in the next 6-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Regarding comorbidities, a multidomain prolonged intervention including diet, physical exercise, cognitive training, and vascular risk factors monitoring could reduce the onset of new comorbidities, as already demonstrated in a younger population (Marengoni et al, 2018). It is then necessary to investigate whether similar or different multidimensional interventions may prove effective also in the last period of life, in preventing/postponing disability (Cecchi et al, 2009) and in effectively prolonging lifespan (Ackermann, 2018). Moreover, it has been suggested that polypharmacy per se increases the risk of mortality (Błeszyńska et al, 2020) as well as of disability (Cecchi et al, 2020) due to the high risk of negative drug interaction and to the higher vulnerability to side effects in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding comorbidities, a multidomain prolonged intervention including diet, physical exercise, cognitive training, and vascular risk factors monitoring could reduce the onset of new comorbidities, as already demonstrated in a younger population (Marengoni et al, 2018). It is then necessary to investigate whether similar or different multidimensional interventions may prove effective also in the last period of life, in preventing/postponing disability (Cecchi et al, 2009) and in effectively prolonging lifespan (Ackermann, 2018). Moreover, it has been suggested that polypharmacy per se increases the risk of mortality (Błeszyńska et al, 2020) as well as of disability (Cecchi et al, 2020) due to the high risk of negative drug interaction and to the higher vulnerability to side effects in the elderly population.…”
Section: Discussionmentioning
confidence: 99%